Encyclopaedia Britannica 2003 ultimate reference suite. - Encyclopaedia Britannica Australia (Australia Encyclopaedia Britannica, 2003)
Contains Encyclopaedia Britannica, Britannica Student Encyclopedia, and Britannica Elementary Encyclopedia, 91,000 articles, dictionaries a world atlas and 21,000 images and videos.
Includes one (1) installation disc and two (3) data discs.
Keywords: Electronic encyclopedias; Encyclopedias and dictionaries